Prognostic impact of ReTURB in high grade T1 primary bladder cancer - Roberto Sanseverino (Archivio Italiano di Urologia e Andrologia, 2016)
Purpose: To evaluate whether pathological outcomes of ReTURB have a prognostic impact on recurrence and progression of primitive T1HG bladder cancer. Material and methods: Patients affected by primitive T1HG TCC of bladder underwent restaging TURB (ReTURB). Patients with muscle invasive disease at ReTURB underwent radical cystectomy; those with non-muscle invasive residual (NMI-RT) and those with no residual tumour (NRT) received an intravesical BCG therapy. We compared recurrence and progression in NMIRT patients and NRT patients at restaging TURB. Patients were followed every 3-6 months with cystoscopy and urine cytology. Results: 212 patients were enrolled in the study. At ReTURB, residual cancer was detected in 92 of 196 (46.9%) valuable patients: 14.3% of these were upstaged to T2. At follow up of 26.3 ± 22.8 months, there were differences in recurrence and progression rates between NRT and NMIRT patients: 26.9% and 45.3% (p < 0.001), 10.6% and 23.4% (p 0.03), respectively. Recurrence-free and progression-free survivals were significantly higher in NRT compared to NMIRT patients: 73.1% and 54.7% (p < 0.001), 89.4% and 76.6 (p 0.03), respectively. Conclusions: ReTURB allows to identify a considerable number of residual and understaged cancer. Patients with NMIRT on ReTURB have worse prognosis than those with NRT in terms of recurrence and progression free survival. These outcomes seem to suggest a prognostic impact of findings on ReTURB that could be a valid tool in management of high grade T1 TCC.